An experimental study on the mechanical behaviour of bonded and hybrid bonded-bolted composite joints using digital image correlation (DIC) technique. (15th November 2021) - Kim, JiHyun; Lopez-Cruz, Pedro; Heidari-Rarani, Mohammad; Lessard, Larry; Laliberté, Jeremy
Abstract: Most studies usually use load-displacement curve or post-failure analysis to understand the mechanical behaviour of hybrid bonded-bolted (HBB) joints. While load sharing in HBB joints is the crucial design parameter and it is important to capture strain field changes or failures under real-time loading conditions. Therefore, two-dimensional digital image correlation (2D-DIC) technique is applied to experimentally investigate the behaviour of bonded and HBB composite joints under quasi-static tensile loading. A flexible epoxy paste adhesive is used. The bonded joint had a hole in the centre to determine the effect of the difference between the stress concentration due to the existence of the hole and the additional stress around a hole due to installation of the bolt. The strain fields around the bolt in a HBB joint and around the open hole in a bonded joint were compared accurately. The DIC technique was able to effectively and rapidly measure the strain field and identify the onset of failure around the fastener during the tests. Finally, the advantages and disadvantages of the DIC technique compared to the classical similar techniques for characterizing the composite joints are briefly explained.